Jahn. ([Place of publication not identfied] : [Publisher not identified])
Helmut Jahn is world-famous for buildings like Frankfurter Messeturm (1985-1991), Sony Center with the Bahntower, Berlin (1993-2000), airport Bangkok-Suvarnabhumi (1995- 2005) and the Veer Towers, Las Vegas (2006-2010). In a luxury edition this book shows in large scale and high-quality photos by the well-known photographer Rainer Viertlböck the increasing international reach of Helmut Jahn's oeuvre, starting in Chicago and the United States in the 1980s and expanding initially to South Africa, then to Europe, with the focus on Germany, and from there via the Middle East to China, Singapore, Japan and Korea.
Jahn+visions.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid
Keywords: Jahn, Helmut, -- 1940-; Architecture, American -- History -- 20th century; Architecture, American -- History -- 21th century; Architecture, German -- History -- 20th century; Architecture, German -- History -- 21th century